Analysis of Code Switching in Basboi Song“Happy Birthday” - Marginingsih, Marginingsih; Nugrahaningsih, Widi; Arintawati, Desi (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
This study uses a qualitative descriptive method.This study aims to analyze the types and reasons for using code switching in the Basboi song entitled Happy Birthday. The data source for this study was taken from the lyrics of the happy birthday song by Basboi. In analyzing the types of code switching, researchers use the theory of Romaine, namely inter-sentential switching, intra-sentential switching and tagswitching. After doing the analysis, there are 2 types of code switching found in this study, namely inter-sentential switching of 2 data, and intra-sentential switching of 9 data. In this research, there was only one reason for using code switching which was found, namely repetition of 1 data.